The Effect of Independent Commissioners, Supply Chain Management, and Audit Committee on Accounting Conservatism - Einde Evana (International Journal of Supply Chain Management, 2020)
Abstract- This study aims to examine the influence of independent commissioner, supply chain management, and audit committee on the accounting conservatism. The accounting conservatism is measured by accrual measurement. The population of this study is manufacturing’scompanies listed on Indonesia Stock Exchange in 2012-2015. Based on purposive sampling method, the total obtained sampleis 508 companies.The source of data is taken from annual reports of companies listed on Indonesia Stock Exchange in 2012-2015.The data analysis method is using multiple linear regressions with SPSS 22 software application.The result of this study found that supply chain management has significant negative effect on the accounting conservatism, while the variables of independent commissioner and audit committee have no significant effect on the accounting conservatism.